2017
DOI: 10.1016/j.copbio.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Time is ripe: maturation of metabolomics in chronobiology

Abstract: Sleep and circadian rhythms studies have recently benefited from metabolomics analyses, uncovering new connections between chronobiology and metabolism. From untargeted mass spectrometry to quantitative nuclear magnetic resonance spectroscopy, a diversity of analytical approaches has been applied for biomarker discovery in the field. In this review we consider advances in the application of metabolomics technologies which have uncovered significant effects of sleep and circadian cycles on several metabolites, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…In addition, drug‐induced changes in cardiac repolarisation depend on the time of day (Kervezee et al., ). The profound influence of the circadian system on metabolism is supported by metabolomic studies that have shown circadian variation across many classes of metabolites, including amino acids, acylcarnitines and lipids (Chua et al., ; Dallmann, Viola, Tarokh, Cajochen, & Brown, ; Davies et al., ; Giskeodegard, Davies, Revell, Keun, & Skene, ; Rhoades, Sengupta, & Weljie, ). Nevertheless, it should be noted that the relationship between the circadian system and metabolism is bidirectional (Brown, ).…”
Section: Metabolic and Cardiovascular Effects Of Circadian Misalignmementioning
confidence: 99%
“…In addition, drug‐induced changes in cardiac repolarisation depend on the time of day (Kervezee et al., ). The profound influence of the circadian system on metabolism is supported by metabolomic studies that have shown circadian variation across many classes of metabolites, including amino acids, acylcarnitines and lipids (Chua et al., ; Dallmann, Viola, Tarokh, Cajochen, & Brown, ; Davies et al., ; Giskeodegard, Davies, Revell, Keun, & Skene, ; Rhoades, Sengupta, & Weljie, ). Nevertheless, it should be noted that the relationship between the circadian system and metabolism is bidirectional (Brown, ).…”
Section: Metabolic and Cardiovascular Effects Of Circadian Misalignmementioning
confidence: 99%
“…We posit that sleep restriction/deprivation leads to a metabolic setting that could resemble aging and may serve as lead to understand the connection of sleep loss and incident neurodegenerative disorders. Comparison of some recent aging metabolomics studies [47][48][49][50][51][52] and sleep metabolomics studies [61] reveals a striking signature of metabolic similarity. We have analyzed recent aging metabolomics literatures ( Fig.…”
Section: Metabolomics Studies Of Experimental Sleep Deprivationmentioning
confidence: 99%
“…The connection between metabolism and sleep has become increasingly established [61]. For exam- Fig.…”
Section: Metabolomic Investigation Of Sleep and Crossover With Aging mentioning
confidence: 99%
See 2 more Smart Citations